Roles of mTORC1 and mTORC2 in controlling γδ T1 and γδ T17 differentiation and function - Yang, Quanli (Cell Death Differ, 2020)
The metabolism-controlled differentiation of αβ T cells has been well documented; however, the role of a metabolism program in γδ T cell differentiation and function has not been clarified. Here, using CD2-cre; mTORC1 Raptor-f/f, and mTORC2 Rictor-f/f mice (KO mice), we found that mTORC1, but not mTORC2, was required for the proliferation and survival of peripheral γδ T cells, especially Vγ4 γδ T cells. Moreover, mTORC1 was essential for both γδ T1 and γδ Τ17 differentiation, whereas mTORC2 was required for γδ T17, but not for γδ Τ1, differentiation. We further studied the underlying molecular mechanisms and found that depletion of mTORC1 resulted in the increased expression of SOCS1, which in turn suppressed the key transcription factor Eomes, consequentially reducing IFN-γ production. Whereas the reduced glycolysis resulted in impaired γδ Τ17 differentiation in Raptor KO γδ T cells. In contrast, mTORC2 potentiated γδ Τ17 induction by suppressing mitochondrial ROS (mitoROS) production. Consistent with their cytokine production profiles, the Raptor KO γδ T cells lost their anti-tumor function both in vitro and in vivo, whereas both Raptor and Rictor KO mice were resistant to imiquimod (IMQ)-induced psoriasis-like skin pathogenesis. In summary, we identified previously unknown functions of mTORC1 and mTORC2 in γδ T cell differentiation and clarified their divergent roles in mediating the activity of γδ T cells in tumors and autoimmunity.